E-Government Integration of Sidoarjo Regency using Service Oriented Architecture (SOA) - Adi Putra Utama; Rengga Asmara; Jauari Akhmad Nur Hasim (IJNMT (International Journal of New Media Technology), 2019)
the slow process of government services is a major problem of current government service systems (e-government). This is due to the lack of integration between e-government systems with regional governments. The application of data integration can accelerate the process of interaction and communication between agencies in the regional government. This study aims to develop an integrated e-government from various services that exist in government services in Sidoarjo Regency. The architecture used in developing this integration is using the Service Oriented Architecture (SOA). In the e-government development process has 3 main stages, namely: database creation, service creation, and service implementation on the frontend. The results of this study are in the form of conclusions on the architectural capabilities used in e-government integration accompanied by the speed of services produced.